2012
DOI: 10.1044/aac21.4.159
|View full text |Cite
|
Sign up to set email alerts
|

Peer-Mediated AAC Instruction for Young Children With Autism and other Developmental Disabilities

Abstract: Many young children with developmental disabilities (DD) have significant delays in social, communication, and play skills. For those children learning to use augmentative and alternative communication (.AAC% successful social interactions with peers will require explicit instruction on the same system for both communication partners. Peer-mediated (PM) interventions are recommended best practice based on more than 30 years of research with young children with autism and other DDs. Integrating direct AAC instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Studies were excluded based on the following criteria: (1) the article was written in a language other than English; (2) the study design was a case study; (3) the play intervention was a form of play therapy; (4) participants included children outside of the pre-defined age range (3-13 years) who could not be isolated from the overall sample with regard to the effect of the intervention; and (5) play was used as part of a multi-component intervention approach alongside strategies including peer training sessions (e.g. Brock et al, 2018;Hu et al, 2018;Kamps et al, 2014;Katz & Girolametto, 2013;Kuhn et al, 2008;Laushey & Heflin, 2000;Lee et al, 2007;Maich et al, 2018;Thiemann-Bourque, 2012;Whitaker, 2004), direct teaching sessions (e.g. Szumski et al, 2016Szumski et al, , 2019 or other naturalistic classroom activities including snack or toilet (e.g.…”
Section: Eligibility Criteria and Study Selectionmentioning
confidence: 99%
“…Studies were excluded based on the following criteria: (1) the article was written in a language other than English; (2) the study design was a case study; (3) the play intervention was a form of play therapy; (4) participants included children outside of the pre-defined age range (3-13 years) who could not be isolated from the overall sample with regard to the effect of the intervention; and (5) play was used as part of a multi-component intervention approach alongside strategies including peer training sessions (e.g. Brock et al, 2018;Hu et al, 2018;Kamps et al, 2014;Katz & Girolametto, 2013;Kuhn et al, 2008;Laushey & Heflin, 2000;Lee et al, 2007;Maich et al, 2018;Thiemann-Bourque, 2012;Whitaker, 2004), direct teaching sessions (e.g. Szumski et al, 2016Szumski et al, , 2019 or other naturalistic classroom activities including snack or toilet (e.g.…”
Section: Eligibility Criteria and Study Selectionmentioning
confidence: 99%
“…Given that language input and modeling by teachers is often low during classroom interactions (Brady, Herynk, & Fleming, 2010), additional input by peers could bolster the amount of communication input (both speech and AAC) that is likely to improve child language development. Thiemann-Bourque (2012) reported that, following a peer-mediated social intervention training on use of PECS, four children with autism increased their average communication acts to peers using PECS from 0 in baseline to 4.4 per 6-min play session, and peers increased their use of PECS materials directed towards play partners with autism from 0.2–7.4 per session, that is, peer initiations and responses using PECS increased after they were specifically taught how to use the same AAC system as the children with autism, which supports more opportunities for language modeling and social interactions for these children.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, peers can be important communication partners when implementing AAC interventions (Bourque, 2020). Peers can help model and teach the AAC system, use the AAC system to converse with the child, and encourage social interaction using the AAC systems and strategies (Thiemann-Bourque, 2012). When children have peers who use AAC strategies and communicate with them using their AAC system, they experience significantly more language growth than children who do not have peer support (Barker et al, 2013).…”
Section: Common Mythsmentioning
confidence: 99%